2021
DOI: 10.1002/adfm.202009946
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell Microgels for Diagnostics and Therapeutics

Abstract: Cell encapsulation within hydrogel droplets is transforming what is feasible in multiple fields of biomedical science such as tissue engineering and regenerative medicine, in vitro modeling, and cell-based therapies. Recent advances have allowed researchers to miniaturize material encapsulation complexes down to single-cell scales, where each complex, termed a singlecell microgel, contains only one cell surrounded by a hydrogel matrix while remaining <100 μm in size. With this achievement, studies requiring si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 317 publications
(471 reference statements)
0
10
0
Order By: Relevance
“…Cell encapsulation can take on different forms, single-cell encapsulation or encapsulation of small cell clusters as covered in these relevant reviews [ 6 , 12 15 ]. Single cell encapsulation offers a defined way of engineering materials for implants.…”
Section: Key Considerations For Cell Microencapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell encapsulation can take on different forms, single-cell encapsulation or encapsulation of small cell clusters as covered in these relevant reviews [ 6 , 12 15 ]. Single cell encapsulation offers a defined way of engineering materials for implants.…”
Section: Key Considerations For Cell Microencapsulationmentioning
confidence: 99%
“…As such multiple in vivo and clinical trials have been performed to demonstrate the therapeutic capabilities of microencapsulation in various disease models (Tables 1 and 2 ). The use of alginate, alone or in combination with other polymers, remains a popular choice due to the familiarity of the material; however, alternate natural and synthetic polymers utilised include polyethylene glycol (PEG), agarose, hydroxyethyl methacrylate (HEMA), methyl methacrylate (MMA), or dextrans [ 15 , 50 , 51 ].
Fig.
…”
Section: Mechanics Of Microencapsulationmentioning
confidence: 99%
“…In such a system, cells can be delivered to a targeted site through less invasive injection to achieve tissue regeneration, so as to effectively achieve cell therapy in tissue engineering and regenerative medicine. [ 120–129 ] For instance, Lipke et al. encapsulated human induced pluripotent stem cells (hiPSCs) in PEG‐fibrinogen gel microspheres fabricated by photo‐crosslinking strategy.…”
Section: Cells and Drugs Related Biomedical Applications Determined B...mentioning
confidence: 99%
“…In such a system, cells can be delivered to a targeted site through less invasive injection to achieve tissue regeneration, so as to effectively achieve cell therapy in tissue engineering and regenerative medicine. [120][121][122][123][124][125][126][127][128][129] For instance, Lipke et al encapsulated human induced pluripotent stem cells (hiPSCs) in PEG-fibrinogen gel microspheres fabricated by photo-crosslinking strategy. The results revealed that the encapsulated hiPSCs began cardiac differentiation on the third day and gradually formed a functional cardiac tissue-like microsphere.…”
Section: Cell Delivery System Based On Single Structure Mprsmentioning
confidence: 99%
“…droplet microfluidics, vibrating jet, inkjet, jet cutting, electrospraying, air-induced spraying) that offered unprecedented advantages, including high-throughput analysis of single cells, biomimetic 3D microenvironments, improved tissue engineering, and cell-based therapy [49]. Another review reports differences on single-cell microgel based on natural (agarose, collagen, hyaluronic acid, etc) and synthetic (PEG and polyacrylate derivatives) hydrogels fabricated by extrusion-based single-cell and microfluidic-based droplet generation as promising tools to understand and direct complex biological systems and cell behaviors as well as enhanced in vitro cell culture, diagnostics, and screening and in vivo therapeutics [52]. The overview of the major developments on microgel-based 3D cell culture at single-cell level is listed in Table 2, whereas the most representative examples are shown in Figure 2.…”
Section: Single Cell Culturementioning
confidence: 99%